Assessing the role of leadership in continuous intention of enterprise resource planning - Azadeh Rezvani, 1979-; Mohammad Nazir Ahmad @ Sharif; Fakulti Sains Komputer dan Sistem Maklumat (2013)
Thesis (Sarjana Sains (Teknologi Maklumat - Pengurusan)) - Universiti Teknologi Malaysia, 2013